Tuberculosis pulmonar y extrapulmonar en gestantes atendidas en el Hospital Regional de Loreto entre los años 2015 y 2021 - Llaiqui Lobon, Roberto Carlos (2024)
GENERAL OBJECTIVE: To determine the clinical characteristics of pulmonary and extrapulmonary tuberculosis among pregnant women treated at the Loreto Regional Hospital between 2015 and 2022. MATERIALS AND METHODS: Quantitative and cross-sectional study. The population will be all pregnant women hospitalized between 2015 and 2022 with a diagnosis of both pulmonary and extrapulmonary tuberculosis at the Regional Hospital of Loreto. The sample will be the same population. The data will be presented in a descriptive way and the analysis will be with a test of proportions. The analysis will be performed in SPSS v26. CONCLUSIONS: The characteristics associated with pulmonary and extrapulmonary tuberculosis in pregnancy present a morbidity risk for both the pregnant woman and the fetus at the Regional Hospital of Loreto.